2016
DOI: 10.1111/aor.12784
|View full text |Cite
|
Sign up to set email alerts
|

Low Tidal Volume Reduces Lung Inflammation Induced by Liquid Ventilation in Piglets With Severe Lung Injury

Abstract: Total liquid ventilation (TLV) is an alternative treatment for severe lung injury. High tidal volume is usually required for TLV to maintain adequate CO clearance. However, high tidal volume may cause alveolar barotrauma. We aim to investigate the effect of low tidal volume on pulmonary inflammation in piglets with lung injury and under TLV. After the establishment of acute lung injury model by infusing lipopolysaccharide, 12 piglets were randomly divided into two groups, TLV with high tidal volume (25 mL/kg) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…This latter finding strengthens a long-held belief within our team that total volume of PFC within the lungs must be tightly regulated. A recent study also suggested the use of lower volumes to prevent lung inflammation during TLV [ 22 ], in keeping with the overwhelming evidence that volutrauma is a significant contributor to ventilator-induced lung injury during conventional mechanical ventilation [ 23 ]. Thus, we hypothesize that uncontrolled volumes of PFC within the lung and/or high pause inspiratory and expiratory pressures may affect cardiac function, which may explain earlier findings of instability with less advanced TLV devices.…”
Section: Discussionmentioning
confidence: 81%
“…This latter finding strengthens a long-held belief within our team that total volume of PFC within the lungs must be tightly regulated. A recent study also suggested the use of lower volumes to prevent lung inflammation during TLV [ 22 ], in keeping with the overwhelming evidence that volutrauma is a significant contributor to ventilator-induced lung injury during conventional mechanical ventilation [ 23 ]. Thus, we hypothesize that uncontrolled volumes of PFC within the lung and/or high pause inspiratory and expiratory pressures may affect cardiac function, which may explain earlier findings of instability with less advanced TLV devices.…”
Section: Discussionmentioning
confidence: 81%
“…Jiang et al of Zhejiang University, Hangzhou, China investigated total liquid ventilation (TLV) in piglets with severe lung injury. Twelve piglets were randomly divided into two groups, TLV with high tidal volume (25 mL/kg) or with low tidal volume (6 mL/kg) for 240 min, respectively.…”
Section: Pulmonary Supportmentioning
confidence: 99%
“…knowledge, the effect of tidal volume and respiratory rate on lung inflammation during TLV has not been thoroughly addressed. Jiang et al (2016) showed that a tidal volume of 6 mL/kg was associated with lower transcription and plasma protein levels of IL-6 and IL-8 in piglets, compared to a higher tidal volume of 25 mL/kg during TLV (Jiang et al, 2016). The authors, however, had to use extracorporeal carbon dioxide removal to achieve acceptable blood-gas exchange, thus preventing the need for high minute ventilation and its potential impact on VILI occurrence.…”
Section: Introductionmentioning
confidence: 99%